PENGARUH SINAR ULTRA VIOLET TERHADAP PERTUMBUHAN BAKTERI Bacillus sp. SEBAGAI BAKTERI KONTAMINAN - T Ariyadi; S. Sinto Dewi (JURNAL KESEHATAN, 2009)
Abstract Microorganisms are in anywhere, as in soil, dust, air, water, food or surface of our body tissues. The existence of these microorganisms was that benefit human life, but many are also harmful as it may cause human diseases or may even cause damage from contamination. Control of microorganisms can be done w it h ultra-violet radiation. The purpose of this study was to determine the influence of duration of irradiation on the growth of bacteria nacillus sp. Type of research is to experiment. Research conducted at the Laboratory of Microbiology Faculty of Nursing and Health, University of Muhammadiah Semarang in May-July 2008.-The sample was Take one coloni of bacteria Bacillus sp. then make a suspension with a density of 2 mc Farmland. Observations were made by observing the number of colonies of Bacillus sp. That grows on long exposures compared to controls without irradiation. Based on our research has been done in the microbiology laboratory results obtained Fikkes unimus, ultra violet irradiation time 38 watts for I minute with a distance of 45 cm on NA medium containing the bacteria Bacillus sp colonies obtained many as l8 fruits, irradiation for 5 minutes and get 15-colony , irradiation for l0 minutes there was no colony grew, irradiation for t5 minutes there was no colony grew. ln control medium not exposed to ultra violet colony growth obtained a very full / not be calculated. Keywords: Bacterial Contamination, Bacillus Sp, Ultra Violet